Black Hammer. Volume 7, Reborn. Part III - Lemire, Jeff (Dark Horse Books, 2022)
"Things have gotten crazy in Black Hammer! First a parallel Spiral City collided with the actual one spawning a multiverse nightmare of heroes and villains from both worlds going to war, and now Lucy Weber picks back up the mantle of Black Hammer and teams up with Skulldigger for answers on how to end the madness. Collects issues #9-#12 of Black Hammer: Reborn. "Jeff Lemire's story is leading to something major as Black Hammer: Reborn nears the final issue [. . .] I am really eager to see where this all is leading."-DC Comic News "Black Hammer: Reborn #9 is the biggest proof of the idea this series will always have your back."-ComicBook.com"--